2006
DOI: 10.1002/jms.995
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of flavonol 3,7‐di‐O‐glycosides and determination of the glycosylation position by using negative ion electrospray ionization tandem mass spectrometry

Abstract: Flavonol 3,7-di-O-glycosides were investigated by negative ion electrospray ionization tandem mass spectrometry using a quadrupole linear ion trap (LIT) mass spectrometer. The results indicate that the fragmentation behavior of flavonol 3,7-di-O-glycosides is substantially different from that of their isomeric mono-O-diglycosides. In order to characterize a flavonoid as a flavonol 3,7-di-O-glycoside, both [Y3(0) - H]-* and [Y(0) - 2H]- ions should be present in [M - H]- product ion spectrum. The MS(3) product … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
231
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 211 publications
(251 citation statements)
references
References 34 publications
15
231
1
Order By: Relevance
“…Since the shoulder absorption of these flavonoids is characteristically different from the podophyllotoxin-type lignans, the use of a wavelength above 300 nm is preferred in the analysis of the flavonoids. Compounds (8) and (11) [36]. Therefore, peaks 2 and 3 are proposed to be quercetin-3-O-glucopyranoside and kaemferol-3-O-glucopyranoside, which have previously been isolated from S. emodi [37].…”
Section: Identification Of Flavonoids In Fingerprint Chromatogramsmentioning
confidence: 96%
“…Since the shoulder absorption of these flavonoids is characteristically different from the podophyllotoxin-type lignans, the use of a wavelength above 300 nm is preferred in the analysis of the flavonoids. Compounds (8) and (11) [36]. Therefore, peaks 2 and 3 are proposed to be quercetin-3-O-glucopyranoside and kaemferol-3-O-glucopyranoside, which have previously been isolated from S. emodi [37].…”
Section: Identification Of Flavonoids In Fingerprint Chromatogramsmentioning
confidence: 96%
“…[20 -24] Previous research revealed that the formation of the aglycone ion (Y 0 − ) and the radical aglycone ion ([Y 0 − H] −• ) plays a significant role in the structural elucidation and differentiation of flavonoid O-glycoside isomers. [20,21] The formation of [Y 0 − H] −• ion has been determined from the product ion spectrum of genistein 7-O-glucoside using time-of-flight MS at high mass resolution. [22] However, there have been few systematic investigations on the characteristic fragmentation of a group of isoflavonoids using tandem mass spectrometric techniques (MS/MS).…”
Section: Introductionmentioning
confidence: 99%
“…MS/MS Analysis for the structural characterization of glycosyl flavonoids has been recently reviewed [15] [16].…”
mentioning
confidence: 99%